A review on medical imaging synthesis using deep learning and its clinical applications. Issue 1 (11th December 2020) - Wang, Tonghe; Lei, Yang; Fu, Yabo; Wynne, Jacob F.; Curran, Walter J.; Liu, Tian; Yang, Xiaofeng
Abstract: This paper reviewed the deep learning‐based studies for medical imaging synthesis and its clinical application. Specifically, we summarized the recent developments of deep learning‐based methods in inter‐ and intra‐modality image synthesis by listing and highlighting the proposed methods, study designs, and reported performances with related clinical applications on representative studies. The challenges among the reviewed studies were then summarized with discussion.